GE_GERICHTE P/72/2015 vom 11. Oktober 2019 - GE Cour de justice (2019)
QUALITÉ POUR AGIR ET RECOURIR;LÉSÉ;CESSIONNAIRE;BLANCHIMENT D'ARGENT;USAGE DE FAUX(DROIT PÉNAL) | CPP.104; CPP.115; CPP.118; CP.251; CP.305B